Proteção de dados pessoais sensíveis em saúde pública : uma análise dos limites no tratamento independente de consentimento - Braga , Isabella Furtado Bacellar Fortes (2022)
Based on the permissive contained in Art.11, item II, subparagraph b, of Law 13,709/2018, regarding the possibility of processing sensitive data regardless of consent, there is a need to affix interpretative beacons for the treatment and sharing of sensitive data in health aimed at the development of epidemiological public policies.Starting from this central question and the driving problem as to which interpretative limits these would be, the investigation of this study, with a qualitative ambience, using the inductive, monographic method, and being based on a bibliographic and documentary exploratory technique, prints as specific objectives , the analysis of the historical, social and legal factors that culminated in the genesis of an autonomous right to data protection and a specific protective law in the Brazilian context; the parameter approach for the development of epidemiological public policies through computerization and operation with sensitive data and in the face of the apparent conflict between the fundamental rights to data protection and informational self-determination and the right to health and life; verification of the process of practical implementation of the National Data Protection Authority, in light of the legal and regimental provisions and, in this sense, to assess the limits regarding the independent treatment of the user's consent act, highlighting the role that this authority plays in that process. The concluding conclusions point out, initially in the sense that the limits attached to Art.11, item II, b are those in line with an integral interpretation of the General Data Protection Law , to reveal and promote effectiveness to the principles and foundations provided for in the law, as well as an interpretation compatible with the constitutional dictates and to reveal a rational ethics in such processing activity, concerned with promoting the greatest possible zeal for the fundamental rights of users and data subjects. With regard to the second final consideration asserted, it refers to the salutary role that the national authority has in this context, both as a contribution to the posting of such interpretative outlines of the device, as well as to promote the inspection that, once established, is also implemented in the practical, to promote a preventive pedagogical and enlightening action for society in general and, in due course, the public administration, which is responsible for the promotion of policies and provision of health services.